PERCEPTIONS ON THE IMPACTS OF MORPHOLOGICAL CHANGES ON THE LOWER COURSE OF RIVER MAYO-INNE, YOLA SOUTH, ADAMAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Rivers are important natural resources that support the existence of humans and other living organisms right from time immemorial. Despite their significance to human livelihood; changes in their morphology can impact on the socio-economic, cultural and environmental values of the riparian environment. Therefore, this study focused on the perception of the impacts of morphological changes on the lower course of River Mayo-Inne, Yola South, Adamawa State, Nigeria. This was done with the view to examine the perceived impacts of morphological changes on riparian land uses; factors influencing morphological changes and estimate the land area affected by changes in river channel morphology of the study area. An integrated approach of remote sensing, GIS, questionnaire survey and interview, were employed in this study. Descriptive statistics such as percentage and sum were used to analyse the data sets. The results revealed that fishing activities, agricultural land, damage on crops, plantation and residential land use have high impacts in the study area. While grazing land and commercial land uses have medium and low impacts respectively. The perceived factors influencing morphological changes in the study area were: discharge 50.75%, sand mining 17.10%, channel bed siltation 13.15% and urbanization 6.80%; all of which provide 81% of the total response of people living in the riparian environments. The temporal analysis of satellite imageries from 1990 to 2015 revealed that the river channel area increased from 486.34ha to 594.90ha respectively; impacting riparian land uses through bank under cutting, chute cutoffs and meander migration...
Keywords: Impacts; Morphology; Land use; Floodplain; River Channel